(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Climate change is going on and its negative impacts include bio-physical and socio-economic aspects. This is one of most serious threats to food security. To over the impacts, food-crop farmers’ adaptation needs enhancement. This paper aims to improve knowledge on critical points in formulating effective strategy and policy for enhancing food-crop farmers’ adaptation on climate change. The key success to adaptation is participation of farmers and other stakeholders. Therefore, farmers’ adaptation-capacity enhancement strategy is a synergy between farmers’ autonomous adaptation and government’s planned adaptation.